A questão da intersubjetividade em O Ser e o Nada - Santos, Vinícius dos (2010)
In Being and Nothingness, Sartre defines man as a hopelessly free being. But thus, iffreedom is our main predicate, would it be possible to think a relationship between differentfreedoms which was not limited to a mere intersubjective conflict, that is, would it be possibleto conceive a theory of the other in Sartre that was not reduced to a clash of freedoms? Theaim of the dissertation is to demonstrate that, despite intersubjectivity be presented in theessay on phenomenological ontology as essentially conflictive, it is possible, already in thisbook, glimpse the overture to think about interpersonal relations of positive reciprocity, thatis, relations able to overcome the inherent conflict of Being-for-others.